Analisa Kualitas Pelayanan dan Kepuasan Konsumen di Perpustakaan - Erny Rachmawati (JBIMA (Jurnal Bisnis dan Manajemen), 2016)
The study 'Analysis of the Quality of Service and the Satisfaction of Students in the Library ' have issue 1) structuring learning place seats rated distance is too short so when learning feels cramped 2) structuring the book is not appropriate place so that confuses students 3) the existence of several bags that are placed on the floor so it looks indestructible. Therefore research objectives 1) to prove the existence of a student complaint among the 5 dimensions of service quality in library 2) to obtain the results of priority instructions on nuclear facilities to improve services. Whose hypotheses H1: the problem that looks physically felt less satisfying than consumer expectations. H2: security issues felt less satisfying than consumer expectations. Method used, each dimension of quality of service contains the items assessed by questions of measurement scale of 1-5 Likert. Further data are analyzed in a descriptive and shown through the table to get an overview of the level of satisfaction. As a result, states that: the problem that looks physically felt less satisfying than the expectations of consumers, are not accepted. Security issues are perceived less satisfying than the expectations of consumers, are not accepted. This means that both hypotheses one and two show results to satisfy consumers.